Father figures [videorecording (DVD)] - Wilson, Owen, 1968-; Helms, Ed; Simmons, J. K.; Bradshaw, Terry; Rhames, Ving, 1961-; Shearer, Harry, 1943-; Squibb, June, 1929-; Walken, Christopher, 1943-; Close, Glenn, 1947- (Warner Bros. Home Entertainment, 2018)
Upon learning that their mother has been lying to them for years about their allegedly deceased father, two fraternal twin brothers hit the road in order to find him.